Perancangan Tutorial Animasi Terhadap Peserta Basic Safety Training Menggunakan Metode Computer Assisted Instruction - Deli Deli (Telcomatics, 2019)
Nowadays, many participants of Basic Safety Training are lack of knowledge about instruction and teachings which has been present by the lecturer in training class regarding Basic Safety Training. Therefore, an application has been designed a programme by using tutorial in animation as supportive equipment for teachings. A Basic Safety Training tutorial in animation application has been developed in this paper. This application is a supportive equipment for teachings which has been held at training class for lecturer to teach Basic Safety Training. This Application is suitable for Personal Computer or Laptop supported by at least Windows 7 Operating System. In designing this application, Computer Assisted Instruction (CAI) method has been implemented. This Basic Safety Training tutorial in animation application is designed by using Adobe Flash Professional CS6 application and other supported applications such as Adobe Photoshop CS3, Adobe Premier Pro CS3, and Adobe Audition.